The Role of Carbon Capture and Storage (CCS) Technology in Coal-Fired Power Plants in Supporting Zero-Emission Policies and National Energy Security - Perdana, Mahendra Yudha; Thamrin, Suyono; Saputro, Guntur Eko (International Journal of Technology and Education Research, 2025)
Coal-fired power plants remain the backbone of Indonesia’s national energy security despite their significant contribution to carbon dioxide (CO₂) emissions. In line with the national Net Zero Emission (NZE) 2060 target, the Indonesian government promotes low-carbon technologies such as Carbon Capture and Storage (CCS). This study discusses the role of CCS in coal power plants in supporting zero-emission policies and national energy security, focusing on implementation effectiveness as well as the driving and inhibiting factors for its adoption in Indonesia. Based on recent literature (2019–2025), CCS demonstrates a strong potential to reduce up to 90% of CO₂ emissions while maintaining reliable domestic energy supply. Key driving factors include extensive geological storage potential, emerging regulatory support, and institutional readiness. However, several obstacles persist, such as high capital costs, regulatory uncertainty, limited infrastructure, and low public acceptance. Therefore, accelerating CCS implementation in Indonesia requires strengthening the regulatory framework, enhancing technical capacity, increasing transparency in storage data, and developing attractive business models. Through these efforts, CCS can serve as a strategic bridge toward a sustainable, low-carbon energy transition.